Pengaruh Persepsi Harga, Kualitas Produk, dan Promosi Penjualan Terhadap Keputusan Pembelian Motor Honda Vario - Stefani, Stefani; Fadillah, Adil (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The purpose of this study is to analyze the effect of price perception, product quality,and sales promotion on purchasing decisions for Honda Vario (Case Study on Consumersin Bogor). Price Perception, Product Quality, and Sales Promotion have an important rolefor the creation of Purchase Decisions. The purposes of this study are (1) to determine theeffect of price perception on purchasing decisions, (2) to determine product quality onpurchasing decisions. (3) To find out sales promotion on purchasing decisions. (4). Todetermine the effect of perception of price, product quality, and sales promotion togetheraffect purchasing decisions, the number of respondents in this study were 220 respondentswho were taken from those who knew and had bought a Honda Vario motorcycle in BogorCity. The research data was processed using SPSS version 22 . The results of this studyare as follows: (1) Price Perception partially affects purchasing decisions with a t-countvalue greater than t-table ( 4.053 > 1.65 ) and a significant value of 0.000 < 0.05; H0 isrejected H1 is accepted. (2) Product quality partially influences purchasing decisions witha t-count value greater than t-table (3.324 > 1.65) and a significant value of 0.001 <0.05;H0 is rejected H2 is accepted. (3) Sales Promotion partially affects the Purchase Decisionwith a t-count value greater than t-table ( 4.099 > 1.65 ) and a significant value of 0.000 <0.05; H0 is rejected H3 is accepted. (4) Perception of Price, Product Quality, and SalesPromotion simultaneously have a positive and significant effect on Purchase Decisions witha calculated F value greater than F table (518.425 > 2.65) and with a significance value of0.000 and less than (Î± = 5%) = 0.05. (5) The three independent variables (Price Perception,Product Quality, and Sales Promotion) are able to explain the variation in the dependentvariable (Purchase Decision) by 87.8%, while 12.2% Purchase Decision is influenced byother independent variables.Keywords: Price Perception, Product Quality, Sales Promotion, and Purchase Decision